Telepsychiatry acceptability by psychiatrists in Lima during the COVID-19 pandemic - Valle, Rubén (2021)
Introduction. The COVID-19 pandemic has prompted the adoption of telepsychiatry for psychiatric medical care. Objective. To evaluate the acceptability of telepsychiatry by psychiatrists, determine the characteristics of telepsychiatric care and request recommendations for the improvement of the telepsychiatry service. Methods. A virtual survey was administered to psychiatrists of the three main psychiatric hospitals in Lima from June 16 to July 16, 2020. Results. 42.9% had worked in telepsychiatry and 57.2% perceived high congruence (80% -100%) between telepsychiatry and face-to-face care. The global mean and in each of the five domains of the acceptability index was above the average. The main recommendation was to improve the flow of care. Conclusion. Telepsychiatry is a modality of care accepted by psychiatrists, this service is expected to improve as problems of daily work are identified and resolved.